(untitled) (CIPEEX, 2022)
CHAPADA DOS VEADEIROS NATIONAL PARK IS LOCATED IN THE STATE OF GOIS. IT IS KNOWN FOR STUNNING GORGES, WATERFALLS AND QUARTZ CRYSTAL FORMATIONS. THE PRETO RIVER HAS ROCKY POOLS AND WATERFALLS. THE BIODIVERSITY PARK IS HOME TO SEVERAL SPECIES OF ORCHIDS AND WILDLIFE, INCLUDING ARMADILLOS, JAGUARS AND TOUCANS. ACCESS TO THE PARK IS VIA THE CITIES OF ALTO PARASO DE GOIS OR SÃO JORGE. ITS MULTIPLE CULTURAL, ENVIRONMENTAL AND BIOLOGICAL NUANCES ARE ONLY PARTIALLY KNOWN, A FACT THAT MARKEDLY LIMITS THE NECESSARY PHYSICAL INTERVENTIONS IN THE REGION. IT IS NECESSARY TO CONSIDER THAT MORE THAN SIXTY-TWO THOUSAND PEOPLE LIVE IN THE CHAPADA DOS VEADEIROS PART AND ARE TRULY RESPONSIBLE FOR ITS CONSERVATION, AND IN PART, FOR ITS REVELATION IN THE PRESENT TIMES. THE WORLD HAS BEEN EXPERIENCING SIGNIFICANT ENVIRONMENTAL CHANGES, WITH DIFFERENT EFFECTS, SOMETIMES INCREASING THE MAGNITUDE OF NATURAL EVENTS, SOMETIMES REDUCING THEIR EFFECTS. THE PRESENT RESEARCH SOUGHT TO DEVELOP ELEMENTS THAT WOULD CONTRIBUTE TO UNDERSTANDING THE CAUSES AND CONSEQUENCES OF THE FAUNA AND FLORA IN CHAPADA DOS VEADEIROS PARK DURING THE COVID-19 PANDEMIC AND TO VERIFY POSSIBLE CAUSES AND CONSEQUENCES OF THE FIRES IN THE PLACE. BIBLIOGRAPHIC RESEARCH WAS CARRIED OUT, THROUGH THEORETICAL REFERENCES AND SCIENTIFIC ARTICLES ALREADY PUBLISHED ON THE SCIELO PLATFORM AND ALSO FIELDWORK IN THE YEARS 2020 AND 2021, DURING THE HEIGHT OF THE PANDEMIC. AFTER THE BIBLIOGRAPHIC SURVEY AND ANALYSIS OF THE SITE VISIT, IT WAS FOUND THAT IN 2020, 552 FIRES WERE REGISTERED IN THE CHAPADA DOS VEADEIROS MICROREGION, ACCORDING TO THE QUEIMADAS DATABASE (BDQ), OF THE NATIONAL INSTITUTE FOR SPACE RESEARCH (INPE). FROM JANUARY TO SEPTEMBER 2021, THERE WERE ALREADY 609 OUTBREAKS. WITH SOCIAL ISOLATION DUE TO THE PANDEMIC, THERE WAS LESS MOVEMENT OF PEOPLE AND VEHICLES. THE LOCAL POPULATION NOTICED THAT THE ENVIRONMENTAL QUALITY OF THE PLACE IMPROVED BY WITNESSING ANIMALS SUCH AS THE JAGUAR AND DEER WALKING AROUND THE CITY; THE CLEAR BLUE COLOR OF THE WATERS OF THE WATERFALLS, ETC. FINALLY, A REFLECTION WAS PROPOSED ON THESE ISSUES THAT SHOULD BE CONSIDERED IN DECISION-MAKING PROCESSES RELATED TO CONSERVATION, MITIGATION AND ADAPTATION TO THE EFFECTS OF FIRES, CLIMATE CHANGE, WHICH SHOULD BE ACCENTUATED IN FUTURE TIMES.